Pentingnya Guru Pendidikan Agama Kristen Dalam Memberikan Pendidikan Seks Kepada Peserta Didik Di SMAS Rentawan Jelimpo - Asnati Asnati; Henni Somantik; Marthen Mau (Pusat riset dan Inovasi Nasional, 2024)
Sex education is very important to give to students because teenagers are vulnerable to misinformation about sexuality. Students when they are teenagers definitely experience many changes and developments, both physically and biologically, therefore guidance is really needed to help them deal with various changes so that they do not experience fear and anxiety about these changes. PAK teachers have duties and responsibilities in educating, motivating, leading and evangelizing students so that they have good moral personalities. This research aims to find out how important it is for PAK teachers to provide sex education to students. Because sex education is given to students to recognize various risky sexual behaviors so that they can be avoided. Apart from that, sex education can also strengthen the personality development of students' lives. The research methodology used in this research is a qualitative methodology with an observation and interview approach. The results of the research theory found by the author are that students need appropriate information about their sex life so that they do not fall into things that are sinful, so that students can become successful people and have a good future. Conclusion: It is very important to provide sex education to students in order to equip students not to carry out any actions that are not in accordance with religious teachings and applicable norms.